Pengaruh Strategi Pemasaran Digital, Citra Merek, dan Loyalitas Pelanggan terhadap Peningkatan Penjualan Kaos Polos CV. Manly Cloth Surakarta - Arwana, Ilham; Ari Susanti (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Fashion companies now have excellent chances to boost sales of their products, even basic T-shirts, thanks to Indonesia's e-commerce's explosive expansion. The purpose of this study is to investigate how customer loyalty, brand image, and digital marketing tactics affect CV. Manly Cloth's ability to increase sales of plain T-shirts. Data instrument tests, multiple linear regression tests, F tests, T tests, and classical assumption tests were used to analyse the study, which used a quantitative approach with 100 respondents via a questionnaire. The findings indicate that while all three factors collectively have a considerable impact on sales growth, only brand image and customer loyalty have a favourable and noteworthy impact, with digital marketing strategy having no discernible influence. In order to boost sales performance on e-commerce platforms, these findings highlight the need of enhancing company image, bolstering client loyalty, and optimising more targeted digital marketing.